2017
DOI: 10.1111/jgh.13458
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic kidney disease have abnormal upper gastro‐intestinal tract digestive function: A study of uremic enteropathy

Abstract: Chronic kidney disease adversely affects digestive function. Abnormalities in digestive secretion and absorption may potentially have a broad impact in the prevention and treatment of both CKD and its complications. Further study is required to assess the factors that contribute to this dysfunction in a wider CKD population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
0
24
1
2
Order By: Relevance
“…This study found that the median GTT was 19 minutes, and to our knowledge, this is the first to report that GTT, per PillCam data, is not prolonged in those with CKD or end-stage renal disease. Uremia in CKD has been associated with gastritis, disruption of the microbiome, and dysmotility disorders [15]. A single magnetic resonance imaging (MRI) study found that gastric emptying was 20 minutes longer in 12 patients with CKD Stage 4/5, but that data conflicts with our findings that GTT via PillCam was only six minutes longer among 21 patients in the CKD 4/5 group [15].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This study found that the median GTT was 19 minutes, and to our knowledge, this is the first to report that GTT, per PillCam data, is not prolonged in those with CKD or end-stage renal disease. Uremia in CKD has been associated with gastritis, disruption of the microbiome, and dysmotility disorders [15]. A single magnetic resonance imaging (MRI) study found that gastric emptying was 20 minutes longer in 12 patients with CKD Stage 4/5, but that data conflicts with our findings that GTT via PillCam was only six minutes longer among 21 patients in the CKD 4/5 group [15].…”
Section: Discussioncontrasting
confidence: 87%
“…Uremia in CKD has been associated with gastritis, disruption of the microbiome, and dysmotility disorders [15]. A single magnetic resonance imaging (MRI) study found that gastric emptying was 20 minutes longer in 12 patients with CKD Stage 4/5, but that data conflicts with our findings that GTT via PillCam was only six minutes longer among 21 patients in the CKD 4/5 group [15]. We are not aware of other studies reporting GTT results by PillCam data among patients with CKD, and our CKD 4/5 cohort is larger than the MRI study.…”
Section: Discussionmentioning
confidence: 99%
“…47 In addition, CKD is associated with prolonged gastric emptying, reduced fasting, and postprandial small bowel water content, indicating abnormal gastrointestinal motility and absorption. 48 Reduced postprandial small bowel water content is correlated with plasma endotoxin level, suggesting that bowel wall edema leads to impaired gut barrier function. 48 Taken together, the current evidence suggests that disruption of gut barrier function in CKD is the major mechanism that allows for the translocation of bacterial fragments to the systemic circulation.…”
Section: Mechanisms Of Bacterial Fragment Translocation In Ckdmentioning
confidence: 99%
“…These factors include low fiber intake due to restricted fruit and vegetable consumption to control serum potassium [83,84], constipation [85][86][87], abnormal digestive function [88], impairment of digestion and absorption of protein [89,90], oral iron supplementation [91], and use of phosphate binders to control serum phosphorus and antibiotics to treat infections [92,93].…”
Section: Gut Microbiota In Ckdmentioning
confidence: 99%